A Plethora of Virulence Strategies Hidden Behind Nuclear Targeting of Microbial Effectors - Rivas, Susana; Genin, Stephane (Frontiers in Plant Science, 2011)
Plant immune responses depend on the ability to couple rapid recognition of the invading microbe to an efficient response. During evolution, plant pathogens have acquired the ability to deliver effector molecules inside host cells in order to manipulate cellular and molecular processes and establish pathogenicity. Following translocation into plant cells, microbial effectors may be addressed to different subcellular compartments. Intriguingly, a significant number of effector proteins from different pathogenic microorganisms, including viruses, oomycetes, fungi, nematodes and bacteria, is targeted to the nucleus of host cells. In agreement with this observation, increasing evidence highlights the crucial role played by nuclear dynamics and nucleocytoplasmic protein trafficking during a great variety of analyzed plant-pathogen interactions. Once in the nucleus, effector proteins are able to manipulate host transcription or directly subvert essential host components to promote virulence. Along these lines, it has been suggested that some effectors may affect histone packing and, thereby, chromatin configuration. In addition, microbial effectors may either directly activate transcription or target host transcription factors to alter their regular molecular functions. Alternatively, nuclear translocation of effectors may affect subcellular localization of their cognate resistance proteins in a process that is essential for resistance protein-mediated plant immunity. Here, we review recent progress in our field on the identification of microbial effectors that are targeted to the nucleus of host plant cells. In addition, we discuss different virulence strategies deployed by microbes, which have been uncovered through examination of the mechanisms that guide nuclear localization of effector proteins.